Role of aromatic alcohol additives on asymmetric organocatalysis reactions: insights from theory - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-an asian jounrnal, 2024)
The presence of an aromatic additive has been seen to enhance, often significantly, the enantioselectivity and yield in asymmetric organocatalysis. Considering their success across a dizzying range of organocatalysts and organic transformations, it would seem unlikely that a common principle exists for their functioning. However, the current investigations with DFT suggest a general principle: the phenolic additive sandwiches itself, through hydrogen bonding and pi & sdot;& sdot;& sdot;pi stacking, between the organocatalyst coordinated electrophile and nucleophile. This is seen for a wide range of experimentally reported systems. That such complex formation leads to enhanced stereoselectivity is then demonstrated for two cases: the cinchona alkaloid complex (BzCPD), catalysing thiocyanation (2-naphthol additive employed), as well as for L-pipecolicacid catalysing the asymmetric nitroaldol reaction with a range of nitro-substituted phenol additives. These findings, indicating that dual catalysis takes place when phenolic additives are employed, are likely to have a significant impact on the field of asymmetric organocatalysis. The current DFT based study, on a wide range of organocatalysis systems, reveals a general principle by which phenolic additives influence asymmetric organocatalysis reactions. It is shown that the phenolic additive forms a sandwich complex, through hydrogen bonding and pi & sdot;& sdot;& sdot;pi stacking interactions, with the organocatalyst coordinated electrophile and nucleophile, and enhances the enantioselectivity of the system as a result. image
Keywords: Additive; Asymmetric Organocatalysis; Cinchona Alkaloid; Density functional theory; Enantioselective Thiocyanation